Eating behavior and its importance for our body - dos Santos , Darlene Pereira; Carvalho , Gleyde Marcia Teixeira Borges; Barros, Henrique Martins; Junior, Carlos Alberto Miranda Duplat; Barros , Joelia Martins (Seven Editora, 2024)
Proper nutrition is essential to ensure a healthy life and a good quality of life. However, many adolescents do not have enough knowledge on the subject and do not adopt a balanced diet. Evidence indicates that unhealthy eating habits are common in this age group, characterized by low consumption of foods such as milk, dairy products, fruits, vegetables and high intake of foods rich in energy, saturated fats, sugars, sodium, such as sugary drinks, sweets and cookies. These practices, associated with a sedentary lifestyle, are risk factors for the development of chronic non-communicable diseases such as overweight, obesity, systemic arterial hypertension, diabetes mellitus, cardiovascular diseases and risk behaviors for eating disorders, which involve a great impact on public health. Thus, in order to avoid health impasses, the importance of food education is highlighted, which is essential for the promotion of health among adolescents in high school. During adolescence, significant changes occur in physical, emotional, and cognitive development, and proper nutrition is essential to ensure healthy growth and development. In view of this situation and considering the great responsibility of the school as an agent of social formation and consequent transformation, the research was developed among students aged between 15 and 19 years. The objective of the research was to understand the eating behavior of these students and verify if they have knowledge about the importance of ingesting vital sources of nutrients. For this, a qualitative research was carried out, through questionnaires, in three public schools in the states of Minas Gerais and Bahia. The data were analyzed and it was possible to observe that the eating patterns and the level of knowledge of the students about healthy eating are insufficient, since they do not worry about having a balanced, nutritious and healthy diet. DOI:https://doi.org/10.56238/sevened2024.025-001